Sunland : A Novel - Waters, Don, 1974- (Book collections on Project MUSE., 2013)
"Sid Dulaney, in his mid-thirties, between jobs and short on funds, has moved back to Tucson to take care of his beloved grandmother. To hold down the cost of her prescriptions, he reluctantly starts smuggling medications over the border. His picaresque misadventures involve the lovable eccentrics at his grandmother's retirement village, Mexican gang threats, a voluptuous former babysitter, midnight voicemails from his exasperated ex-girlfriend, and, perplexingly, a giraffe"--Jacket flap.